Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Ẩn danh

\(\sqrt{12}\)-\(\sqrt{27}\)+\(\sqrt{48}\)

Nguyễn Lê Phước Thịnh
26 tháng 8 2024 lúc 20:08

\(\sqrt{12}-\sqrt{27}+\sqrt{48}\)

\(=2\sqrt{3}-3\sqrt{3}+4\sqrt{3}\)

\(=6\sqrt{3}-3\sqrt{3}=3\sqrt{3}\)

Akai Haruma
26 tháng 8 2024 lúc 20:09

Lời giải:

$\sqrt{12}-\sqrt{27}+\sqrt{48}=2\sqrt{3}-3\sqrt{3}+4\sqrt{3}$

$=(2-3+4)\sqrt{3}=3\sqrt{3}$

Phasnh
26 tháng 8 2024 lúc 20:09

\(\sqrt{12}-\sqrt{27}+\sqrt{48}=2\sqrt{3}-3\sqrt{3}+4\sqrt{3}=3\sqrt{3}\)

ㅤ        ㅤㅤㅤㅤㅤㅤㅤ
26 tháng 8 2024 lúc 20:10

\[
2\sqrt{3} - 3\sqrt{3} + 4\sqrt{3}
\]
\[
(2 - 3 + 4)\sqrt{3} = 3\sqrt{3}
\]

=>  \(3\sqrt{3}\).


Các câu hỏi tương tự
Lương Ngọc Anh
Xem chi tiết
manh
Xem chi tiết
Xem chi tiết
Tuấn Tú
Xem chi tiết
Lương Ngọc Anh
Xem chi tiết
Nguyễn Khánh Nhi
Xem chi tiết
Phạm Duy Thành Đạt
Xem chi tiết
Linh Nguyễn Diệu
Xem chi tiết
Linnz
Xem chi tiết
Ngân Hà Đặng
Xem chi tiết